PENGELOLAAN KAWASAN KOTA LAMA SEMARANG SEBAGAI SALAH SATU KAWASAN PARIWISATA DI KOTA SEMARANG - Grahadwiswara, Agastya; Hidayat, Zaenal; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Various issues such as the absence of government regulation of the regulatory regions of the old city area management, management of the old city area of Semarang and the lack of attention to cultural heritage buildings into the background of this research. This study aims to analyze and describe the management of the old city area of Semarang as one of the tourist area and know the factors that hinder the management. This study used a qualitative research method is descriptive. The results showed that the management of the old city area of Semarang has not demonstrated effective management. Rules are used refers to the Regional Regulation No. 8 of 2003 on Space and Environmental Building (RTBL). Unfortunately, the management function can not be used in the management of the old city area. Management Old Town area of Semarang is inhibited by a variety of factors such as the relevant authorities BPK2L area management, budget and community participation.Based on these conclusions, the researchers recommend to BPK2L as the manager of the old city area. Management needs to be fortified by local regulation that binds to all sectors and seriously support the government to develop and manage the Old Town area of Semarang as one area of tourism in the city of Semarang.